Cucurbitaceae species used as traditional medicine in West Africa - Olufunke O. Fajinmi; Olaoluwa O. Olarewaju; Georgina D. Arthur; Kuben Naidoo; Roger Coopoosamy (AOSIS, 2022)
Background: The use of some Cucurbitaceae species for the treatment of diseases is an ancient practice in traditional medicine systems in Africa and the cucurbitacins among others have been reported to be responsible for most of these healing activities. Aim: This review discusses the relevance of Cucurbitaceae species in traditional medicine in some west African countries. Methods: A literature search was conducted on electronic databases such as Google Books, Google Scholar, Scopus and Web of Science. The search involved the use of several terms and free text words which include 'Cucurbitaceae species in West Africa traditional medicine'; 'medicinal plants of the Cucurbitaceae family used to treat diseases in west African communities'. Results: Several Cucurbitaceae species are used in the region either in similar ways or different ways for the treatment of different diseases. The leaves are the most utilised plant parts and decoctions are the most common method of preparation. From this study, 18 species of Cucurbitaceae used for medicinal purposes were reviewed from Nigeria; 4 from Benin, Ghana, Côte d'Ivoire and Mali, respectively; 1 from Togo; 5 from Senegal; 9 from Cameroon and 3 from Gabon and Burkina Faso, respectively. Momordica charantia and Momordica balsamina are often utilised for abortion in some west African countries. Momordica species and Lagenaria breviflora are utilised to treat diabetes, cough related to respiratory infections and viral infections such as measles and chickenpox Conclusions: In-depth research into these plants could help to develop a natural, novel cure for diabetes and coronavirus (COVID-19) and effective, cheap contraceptive. Contribution: This review highlights the significant role of Cucurbitaceae species in the treatment of a wide range of diseases and health issues in the WestAfrican traditional medicine system. The information provided could be used as a guide by research scientists for the formulation of natural products to cure a variety of diseases.